Pemberian Pakan Burung Berbasis Internet Of Things - Danandjaya Saputra; Albert Aprilio (Prosiding, 2022)
The development of science and technology is currently growing quite rapidly, including the Internet of Things (IoT). Internet of Things (IoT) is one of the new trends in the world of technology that is likely to become one of the big things in the future. IoT is a concept that aims to expand the benefits of continuously connected internet connectivity. This makes the author want to build an IoT that can help the IoT bird feeding process and can be controlled through applications.The methodology used in this study is to use the techniques of Interview, Observation, and Literature Study. And this software development methodology uses the Waterfall (Class Life Cycle) model. Based on the problems that arise, the authors propose a prototype of IoT-based bird feeding, so this application can assist in the process of feeding birds manually or automatically